Understanding ICU Nursing Knowledge, Perceived Barriers, and Facilitators of Sepsis Recognition and Management: A Cross-Sectional Study - Katherine A. Kissel, MN, RN; Karla D. Krewulak, PhD; Thérèse G. Poulin, BSc; Ken Kuljit S. Parhar, MD, MSc; Daniel J. Niven, MD, PhD; Vanessa M. Doiron, MScHQ, RN; Kirsten M. Fiest, PhD (Critical Care Explorations)
IMPORTANCE:. Nursing workforce changes, knowledge translation gaps, and environmental/organizational barriers may impact sepsis recognition and management within the ICU. OBJECTIVES:. To: 1) evaluate current ICU nursing knowledge of sepsis recognition and management, 2) explore individual and environmental or organizational factors impacting nursing recognition and management of sepsis using the Theoretical Domains Framework (TDF), and 3) describe perceived barriers and facilitators to nursing recognition and management of patients with sepsis. DESIGN, SETTING, AND PARTICIPANTS:. This cross-sectional survey was administered to nurses working in four general system ICUs between October 24, 2023, and January 30, 2024. MAIN OUTCOMES AND MEASURES:. Quantitative questions (single/multiple choice, true/false, and Likert-based questions eliciting agreement with a statement) were analyzed using descriptive statistics. Open-ended questions exploring barriers and facilitators to sepsis recognition and management were analyzed using qualitative content analysis. RESULTS:. A total of 101 completed survey responses were retained. Most nurses agreed early sepsis detection saves lives (n = 98, 97%, TDF domain Beliefs About Consequences) and that nursing care can improve patient outcomes (n = 97, 96%, TDF domain Optimism). Fewer nurses agreed it was easy to identify priority sepsis interventions based on order urgency (n = 53, 53%, TDF domain Memory, Attention, and Decision Processes). Reoccurring barriers and facilitators to sepsis recognition and management were commonly identified across the TDF domains of Knowledge, Skills, Environmental Context and Resources, and Social Influences, including competency deficit (with facilitators including support from colleagues), workload or staffing, and equipment or resource availability. CONCLUSION AND RELEVANCE:. ICU nursing sepsis recognition and management is impacted by numerous individual, environmental, and organizational factors. Recommendations include enhanced competency development or support, utilization of structured reinforcement measures (involving the interdisciplinary team and imploring the use of integrative technologies), and addressing equipment/resource-related gaps. Future research and improvement initiatives should use a theory-informed approach to overcome the pervasive, complex challenges impeding timely sepsis recognition and management.